Процедуры распознавания на байесовских сетях для показателей скорости оседания эритроцитов - Гридина, Н.Я.; Вагис, А.А.; Тарасов, А.Л. (Компьютерная математика, 2013)
Использован алгоритм на байесовских сетях по отношению к показателям модифицированной скорости оседания эритроцитов. Построены эффективные байесовские процедуры для этих показателей. Побудовані нові ефективні процедури розпізнавання на основі байєсівських мереж за відношенням до показників модифікованої швидкості осідання еритроцитів при гліомах. Уперше вдалося розрізняти запальні процеси обумовлені гліомами різних ступенів злоякісності поміж собою. Підвищилась ефективність розпізнання запальних процесів при гліомах II ступені злоякісності. New effective procedures of recognition with Bayesian networks for modificated erythrocyte sedimentation rate at gliomas were built. It is first succeeded to distinguish inflammatory processes that are caused with gliomas between each other . It is improved effectiveness of recognition the inflammatory at the II brain gliomas. Efficiency of recognition of inflammatory processes has risen at gliomas of the second degrees of malignantness.